Undiagnosed Type 2 Diabetes Mellitus and Its Risk Factors among Malaysians: Findings of a Nationwide Study - Hasimah Ismail,; Mohd Azahadi Omar,; Anis Aqilah Noor Hisham,; Tahir Aris,; Rashidah Ambak,; Mohammad Fadhli Mohd Yusoff,; Lim, Kuang Kuay (Universiti Kebangsaan Malaysia, 2016)
Introduction: The prevalence of Type 2 diabetes mellitus (T2DM) is increasing worldwide and many of these affected individuals remain unidentified. Undiagnosed T2DM may impose substantial public health implications because these individuals remain untreated and at risk for complications. The objective of this study was to determine the national prevalence of undiagnosed T2DM and to identify the associated risk factors. Methods: A nationwide cross-sectional study was conducted involving 17,783 respondents. Two-stage stratified sampling design was used to select a representative sample of the Malaysian adult population. Structured validated questionnaires with face to face interviews were used to obtain data. Respondents, who claimed that they were not having diabetes, were then asked to perform a fasting blood glucose finger-prick test by Accutrend GC machine. Results: The prevalence of undiagnosed T2DM was 8.9% (n=1587). The highest percentage of undiagnosed T2DM was found among males (10.2%), 55-59 years old (13.4%), highest education attainers of primary school (11.1%), Indians (10.3%), married (10.3%), working (8.9%) and living in the urban areas (9.2%). Multivariate analyses showed that factors associated with undiagnosed T2DM were gender, age group, ethnicity, marital status, obesity and hypertension. Conclusion: This study found an increasing trend of undiagnosed T2DM in Malaysia compared to 2006. This finding is alarming as risk factors associated with undiagnosed diabetes were related to most of the socio-demographic factors studied. Therefore, early diabetic screening is crucial especially among adults aged 30 and above to prevent more serious complications of this disease.